X-ray polarimetry of X-ray pulsar X Persei: another orthogonal rotator? - Mushtukov AA; Tsygankov SS; Poutanen J; Doroshenko V; Salganik A; Costa E; Di Marco A; Heyl J; La Monaca F; Lutovinov AA; Mereminsky IA; Papitto A; et al. (OXFORD UNIV PRESS, 2025)
X Persei is a persistent low-luminosity X-ray pulsar of period of ≈ 835 s in a Be binary system. The field strength at the neutron star surface is not known precisely, but indirect signs indicate a magnetic field above 1013 G, which makes the object one of the most magnetized known X-ray pulsars. Here we present the results of observations X Persei performed with the Imaging X-ray Polarimetry Explorer (IXPE). The X-ray polarization signal was found to be strongly dependent on the spin phase of the pulsar. The energy-averaged polarization degree in 3–8 keV band varied from several to ∼20 per cent over the pulse with a phase dependence resembling the pulse profile. The polarization angle shows significant variation and makes two complete revolutions during the pulse period, resulting in nearly nil pulse-phase averaged polarization. Applying the rotating vector model to the IXPE data we obtain the estimates for the rotation axis inclination and its position angle on the sky, as well as for the magnetic obliquity. The derived inclination is close to the orbital inclination, reported earlier for X Persei. The polarimetric data imply a large angle between the rotation and magnetic dipole axes, which is similar to the result reported recently for the X-ray pulsar GRO J1008−57. After eliminating the effect of polarization angle rotation over the pulsar phase using the best-fitting rotating vector model, the strong dependence of the polarization degree with energy was discovered, with its value increasing from 0 at ∼2 keV to 30per cent at 8 keV.